Penerapan Scientific Approach untuk Meningkatkan Literasi Saintifik dalam Domain Kompetensi Siswa SMP pada Topik Kalor - Ilhami Novili, Widi; Utari, Setiya; Saepuzaman, Duden (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2016)
Abstract Scientific Literacy (SL) is a person's ability to use knowledge and scientific process to understand scientific phenomena in solving a problem or making a decision. However it is known that the SL of Indonesian students are in low grade. There is an indication that the SL is less facilitated in science learning. Capabilities that it is seen difficult associated with evaluating and designing scientific investigations, as well as making the questions for investigation. Quasy-experimental research with one group pretest and posttest design applied in one of the schools in Bandung city through purposive sampling, which consist of 32 students which aim to get the result of the SL after being applied scientific approach to the topic of heat. The instrument uses 20 essays with a reliability of 0.83. N-gain analysis showed an increase in the domain of competence, that is a competence in explaining scientific phenomena, competence in evaluating and designing of scientific research, as well as the competence to interpret the data and scientific evidence.. Learning with applying scientific approach has been able to increase the competency in the medium category. Keywords: scientific approach, scientific literacy, heat Abstrak Literasi Saintifik (LS) merupakan suatu kemampuan seseorang dalam menggunakan pengetahuan dan proses sains untuk memahami fenomena ilmiah dalam memecahkan suatu masalah atau mengambil keputusan. Namun diketahui bahwa LS siswa Indonesia masih rendah. Terdapat indikasi bahwa LS ini kurang terfasilitasi di dalam pembelajaran sains. Kemampuan yang dipandang sulit terkait dengan mengevaluasi dan merancang penyelidikan ilmiah, serta membuat pertanyaan penyelidikan. Penelitian quasy-eksperimen dengan desain one group pretest and posttest diterapkan di salah satu sekolah di kota Bandung melalui purposive sampling dengan jumlah sampel 32 siswa yang bertujuan untuk mendapatkan hasil LS setelah diterapkan scientific approach pada topik kalor. Instrumen menggunakan 20 soal essay dengan reliabilitas 0,83. Analisis N-gain menunjukkan peningkatan pada domain kompetensi yaitu kompetensi menjelaskan fenomena ilmiah, kompetensi mengevaluasi dan merancang penelitian ilmiah, serta kompetensi menginterpretasikan data dan bukti ilmiah. Pembelajaran dengan scientific approach telah dapat meningkatkan domain kompetensi dalam kategori sedang. Kata-kata kunci: scientific approach, literasi saintifik, kalor